Circular economy and consumer's engagement: an exploratory study on higher education - Alves, Wellington (2022)
Background: Circular Economy has been considered one of the most powerful principles of modern society. The concerns about increasing resource consumption have forced governments and companies to look at the circular models as a hedge against resource scarcity and an engine for innovation and growth. Objectives: This research aims to bring together the Circular Economy and the consumer's perspective to perceive the impact of its choices on CE initiatives. Methods/Approach: A survey was conducted considering the consumer's engagement with the circular economy concepts. Results: The results pointed out the awareness and willingness of consumers for the transition from the linear to the circular production model, providing an added value to consumers for reducing environmental impacts. Conclusions: Consumers' behaviour can have a forefront role in building a guide with best practices to be considered by companies, designers, and consumers on implementing initiatives in the field of Circular Economy.